Severe pulmonary hypertension in Ullrich-Noonan syndrome. Issue 1 (July 1989) - Tinker, A; Uren, N; Schofield, J
Abstract : A 19 year old woman with Ullrich-Noonan syndrome presented with a six month history of progressive dyspnoea and cyanosis. Clinical features were suggestive of severe pulmonary hypertension. Cross sectional echocardiography showed pronounced right ventricular pressure overload with right ventricular hypertrophy. Cardiac catheterisation confirmed severe pulmonary hypertension. Attempts to reduce pulmonary artery pressure with calcium channel blockers were unsuccessful. The patient died shortly after investigation. Necropsy confirmed primary pulmonary hypertension.